Tourism at the intersection of animal ethics, human ecology, and conservation: Asian elephants in violation? - Fennell, David; Rizzolo, Jessica Bell; Theerasak, Waraporn; Pookkaman, Nuchjaree; Ittiphong, Kasemsri (Frontiers in Ethology, 2026)
Given the common proposed use of wildlife tourism as a conservation tool, it is essential for conservation practice to determine the differential impacts of wildlife tourism on wildlife themselves in a manner that takes cross-cultural differences into account. With Asian elephants as a case study, this paper developed a conceptual approach (theory synthesis) that integrated the concept of symbiosis from biology, a scale of justice framework from philosophy, tourist typologies from tourism studies, and the concept of inviolate zones from conservation science. This approach case be used to determine the degree of impact different tourist types have on elephants, rendering them as either violate or inviolate “zones”. The paper employed a conceptual approach in the form of theory synthesis, which was later used as a framework from which to investigate how animal-based tourism scholars and students (19 Thai students in five groups after a teaching intervention) perceive 13 different uses of Asian elephants. Results indicate largely consistent responses by the scholars on these uses within the framework, while the consistency of student responses depended upon the type of elephant use examined. The challenges and prospects for a conceptually rigorous, multi-disciplinary evaluation of tourism’s impacts on Asian elephants and other wildlife are discussed.